Leading for equality making schools fairer - Lumby, Jacky; Coleman, Marianne (SAGE Publications Ltd, 2016)
The authors provide an overview of what it means to manage for equality in schools. Whether at senior management or classroom level, issues such as equality of opportunity and outcomes are central to education policy and practice in the UK. The authors explain and disentangle terms like equality, equity, diversity and social justice. This book will be an accessible guide to current thinking on equality, and how this looks in schools. They will reference European and international literature
Keywords: Educational equalization -- Great Britain; Education and state -- Great Britain